Thermal conduction behaviors of chemically cross-linked high-density polyethylenes - Yu, Seunggun; Park, Cheolmin; Hong, Soon Man; Koo, Chong Min (ELSEVIER SCIENCE BV, 2014)
The effect of chemical crosslinking on the thermal conductivity of high-density polyethylene (HDPE) was investigated. The crosslinking density of HDPE was controlled by the content of the crosslinking agent of dicumyl peroxide (DCP) in molten state. As the content of DCP increased, the gel content of HDPE increased, and crystal structure such as spherulite size and crystallite size, and crystallinity decreased, as network formation suppressed the crystallization of polymer molecules. The thermal conductivity of crosslinked HDPE was proportional to the crystallinity and reciprocal to the gel content. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: LINEAR POLYETHYLENE; INTERFACE MATERIALS; MOLECULAR-WEIGHT; LINKING; NANOCOMPOSITES; COMPOSITES; POLYMERS; DEFECTS